Массоперенос при жидкофазной эпитаксии двухслойных систем - Dranchuk, S. M.; Zavadzkii, V. A.; Mokritskii, V. A. (PE "Politekhperiodika", Book and Journal Publishers, 2012)
A liquid phase epitaxy diffusion model of a two-layer system at instable cooling speed of the solution-melt has been developed. It was discovered that the transition process continues even after the termination of cooling, due to which the layer growth continues as well. This effect is connected with to the hypothetical inertia of the diffusion process. The practical application of this phenomenon is shown.